Strategy to increase the double-poling skill of women cross country skiers to an international level - Yoshimoto, D.; Suzuki, T. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The present study aimed to clarify the task for leveling up the skill of women athletes by comparing the gliding motion during double poling in cross-country skiing between male and female athletes.